2020
DOI: 10.1103/physrevb.102.045127
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure beyond the generalized gradient approximation for Ni2MnGa

Abstract: The stability of the nonmodulated martensitic phase, the austenitic Fermi surface and the phonon dispersion relations for ferromagnetic Ni2MnGa are studied using density functional theory. Exchange-correlation effects are considered with various degrees of precision, starting from the simplest local spin density approximation (LSDA), then adding corrections within the generalized gradient approximation (GGA) and finally, including the meta-GGA corrections within the strongly constrained and appropriately norme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…2 a), the use of meta-GGA SCAN +U could result in a better agreement with the experiments. Anyway, SCAN already approaches higher magnetic moments than GGA 47 , 55 , 57 and correctly predicts higher magnetization of austenite over martensite phase in agreement with our results. Therefore, smaller values of the parameter U would be necessary in the meta-GGA + U approach, which is consistent with the metallic nature of the constituent elements.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2 a), the use of meta-GGA SCAN +U could result in a better agreement with the experiments. Anyway, SCAN already approaches higher magnetic moments than GGA 47 , 55 , 57 and correctly predicts higher magnetization of austenite over martensite phase in agreement with our results. Therefore, smaller values of the parameter U would be necessary in the meta-GGA + U approach, which is consistent with the metallic nature of the constituent elements.…”
Section: Discussionsupporting
confidence: 90%
“…An increase in the magnetization calculated by HSE03 was expected due to stronger electron localization and pronounced exchange splitting, as observed in bulk metallic systems 35,36 . Calculations using meta-GGA exchange-correlation functional also predict higher magnetization than GGA 47,55 (see also Supplementary Information SI Figs. 1, 2).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…[145,146] Pioneering calculations for off-stoichiometric compositions were performed by Enkovaara et al, [125] who showed that stability of NM martensite with respect to austenite is stronger in Mn-rich alloys than in stoichiometric alloy. The increased stability of NM martensite was also observed for Nirich alloys by Zayak et al [95] and other authors. [62,147] The validity of this approach for predicting T M was also confirmed for alloys with Fe and Co, [145,146] Al, [97] Pt, [61] Cu, [148] Zn, [124,149] Ti, [150] B, [122] and CoþCu.…”
Section: Search For the Ground State Of Ni 2 Mngasupporting
confidence: 76%
“…[89,[91][92][93] Advanced approximations of the exchange-correlation energy, including dependence on the kinetic energy density, [94] were shown to modify the nesting properties of the austenitic Fermi surface. [95] This, nevertheless, results in an underestimation of the magnitude of the nesting vector but more accurate predictions of the c=a ratio for the NM phase. [90] Valuable results were obtained for the 10M modulated phase under the assumption of smooth harmonic modulations.…”
Section: Search For the Ground State Of Ni 2 Mngamentioning
confidence: 99%